The equation  −3x−9=−21   is solved as follows. Supply the correct numbers to complete the solution.(1 point)

−3x−9=−21 
−3x= ___ Add 9 to both sides.
x= ___Divide both sides by −3.

11 answers

To solve the equation \(-3x - 9 = -21\), we can follow the steps outlined in your question.

  1. Start with the original equation: \(-3x - 9 = -21\)

  2. Add 9 to both sides: \(-3x = -21 + 9\) \(-3x = -12\)

  3. Divide both sides by \(-3\): \(x = \frac{-12}{-3}\) \(x = 4\)

So, filling in the blanks:

  • For \(-3x = ____\): The answer is \(-12\).
  • For \(x = ____\): The answer is \(4\).

Thus, the completed solution is:

  • \(-3x = -12\)
  • \(x = 4\)
The equation  10x+13=−12   is solved as follows. Supply the correct numbers to complete the solution.(1 point)
10x+13=−12 
10x= ___ Subtract 13 from both sides.
x= ___Divide both sides by 10.

To solve the equation \(10x + 13 = -12\), we can follow the steps as outlined:

  1. Start with the original equation: \[ 10x + 13 = -12 \]

  2. Subtract 13 from both sides: \[ 10x = -12 - 13 \] This simplifies to: \[ 10x = -25 \]

  3. Divide both sides by 10: \[ x = \frac{-25}{10} \] This simplifies to: \[ x = -2.5 \]

So, filling in the blanks:

  • For \(10x = ____\): The answer is \(-25\).
  • For \(x = ____\): The answer is \(-2.5\).

Thus, the completed solution is:

  • \(10x = -25\)
  • \(x = -2.5\)
Solve  5−6x=−7 

To solve the equation \(5 - 6x = -7\), follow these steps:

  1. Start with the original equation: \[ 5 - 6x = -7 \]

  2. Subtract 5 from both sides: \[ -6x = -7 - 5 \] Simplifying the right side gives: \[ -6x = -12 \]

  3. Divide both sides by \(-6\): \[ x = \frac{-12}{-6} \] Simplifying this gives: \[ x = 2 \]

Thus, the solution is: \[ x = 2 \]

The equation  5/3x+11/3=−4/3  is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
5/3x+11/3=−4/3
5/3x= ___ Subtract 113 from both sides.
x= ___ Multiply both sides by 35, the reciprocal of 53. 

To solve the equation \(\frac{5}{3}x + \frac{11}{3} = -\frac{4}{3}\), we can proceed with the following steps:

  1. Start with the original equation: \[ \frac{5}{3}x + \frac{11}{3} = -\frac{4}{3} \]

  2. Subtract \(\frac{11}{3}\) from both sides: \[ \frac{5}{3}x = -\frac{4}{3} - \frac{11}{3} \] Simplifying the right side gives: \[ \frac{5}{3}x = -\frac{15}{3} = -5 \]

  3. Multiply both sides by \(\frac{3}{5}\), the reciprocal of \(\frac{5}{3}\): \[ x = -5 \cdot \frac{3}{5} \] Simplifying this gives: \[ x = -3 \]

Now, filling in the blanks:

  • For \(\frac{5}{3}x = ____\): The answer is \(-5\).
  • For \(x = ____\): The answer is \(-3\).

Thus, the completed solution is:

  • \(\frac{5}{3}x = -5\)
  • \(x = -3\)
The equation 0.24x−0.74=−1.1 is solved as follows. Fill in the correct numbers to complete the solution.(1 point)
0.24x−0.74=−1.1
0.24x=____ Add 0.74 to both sides.
x= ____ Divide both sides by 0.24.

To solve the equation \(0.24x - 0.74 = -1.1\), follow these steps:

  1. Start with the original equation: \[ 0.24x - 0.74 = -1.1 \]

  2. Add \(0.74\) to both sides: \[ 0.24x = -1.1 + 0.74 \] Simplifying the right side gives: \[ 0.24x = -0.36 \]

  3. Divide both sides by \(0.24\): \[ x = \frac{-0.36}{0.24} \] Simplifying this gives: \[ x = -1.5 \]

Now, filling in the blanks:

  • For \(0.24x = ____\): The answer is \(-0.36\).
  • For \(x = ____\): The answer is \(-1.5\).

Thus, the completed solution is:

  • \(0.24x = -0.36\)
  • \(x = -1.5\)
Good job 👍 bot

Thank you! I'm glad I could help. If you have any more questions or need further assistance, feel free to ask! 😊👍